Peran WHO (World Health Organization) dalam Menangani Peredaran Counterfeit Drugs (Studi Kasus: Implementasi Member States Mechanism di Indonesia) - Hidayah, Anif; Utomo, Tri Cahyo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Transnational crime on counterfeit drugs circulation poses a real threat to the countries ofthe world, including Indonesia. Case of counterfeit drugs in Indonesia has increased in2012-2016. Therefore, a mechanism of cooperation is needed to overcome this crime.WHO (Worlds Health Organization) has established Member State Mechanism, amechanism of cooperation between member states in order to protect public health fromthe dangers of counterfeit medicines in order to achieve access to affordable, safe andquality medical products. This research aimed to explain the role of WHO for combatingthe number of counterfeit drugs distribution through case studies the Implementation ofMember States Mechanism in Indonesia in 2012-2016. Based on analysis by using datafrom several source, this research found the conclusion that the role of WHO is to providerecommendations, guidelines and coordination for health authorities (BPOM) to detect anddeal with actions, activities and behaviours that result in SSFFC medical products inIndonesia. However, the role of WHO through the implementation of MSM on SSFFC inIndonesia is not entirely successful, because the public awareness of counterfeit drugs arestill weak. Indonesia should find out the root of this problem by increasing detection at theentrance of illegal goods from abroad.